Hoverflies provide pollination and biological pest control in greenhouse-grown horticultural crops - Li, Hui; Wyckhuys, Kris A. G.; Wu, Kongming (Frontiers in Plant Science, 2023)
Beneficial insects provide pollination and biological control in natural and man-made settings. Those ecosystem services (ES) are especially important for high-value fruits and vegetables, including those grown under greenhouse conditions. The hoverfly Eupeodes corollae (Diptera: Syrphidae) delivers both ES, given that its larvae prey upon aphid pests and its adults pollinate crops. In this study, we investigated this dual role of E. corollae in three insect-pollinated and aphid-affected horticultural crops i.e., tomato, melon and strawberry within greenhouses in Hebei province (China). Augmentative releases of E. corollae increased fruit set and fruit weight of all three crops, and affected population dynamics of the cotton aphid Aphis gossypii (Hemiptera: Aphididae). On melon and strawberry, E. corollae suppressed A. gossypii populations by 54-99% and 50-70% respectively. In tomato, weekly releases of 240 E. corollae individuals/100 m2 led to 95% fruit set. Meanwhile, releases of 160 hoverfly individuals per 100 m2 led to 100% fruit set in melon. Also, at hoverfly/aphid release rates of 1:500 in spring and 1:150 in autumn, aphid populations were reduced by more than 95% on melon. Lastly, on strawberry, optimum levels of pollination and aphid biological control were attained at E. corollae release rates of 640 individuals/100 m2. Overall, our work shows how augmentative releases of laboratory-reared hoverflies E. corollae can enhance yields of multiple horticultural crops while securing effective, non-chemical control of resident aphid pests.